Intergroup relations, racism and attribution of natural and cultural traits - Dechamps, J. Claude (2005)
This paper is framed by the general hypothesis according to which racism and xenophobia are today expressed not only in direct ways but also in indirect ways, in ways that protect people from being seen as transgressors of the anti-racist norm. From this general hypothesis we derived specific hypotheses on ingroup favouritism and outgroup derogation at the level of the attribution of natural and cultural traits. We tested the hypothesis that the groups that are object of racialization (black Africans) or etnhicization (people classified as ‘from eastern countries’ and as Muslims) can also be object of ontologisation. Our results show an ingroup favouritism and outgroup derogation of devalued outgroups or of outgroups with inferior social status. Results also show that an out group with a status equal to the one of the ingroup and with common imagined roots is not object of discrimination. Moreover, black Africans are the only group object of ontologisation.